Karakterisasi Produk Biosolubilisasi Lignit oleh Kapang Indigenus dari Tanah Pertambangan Batubara di Sumatera Selatan - Sugoro, Irawan; Hermanto, Sandra; Sasongko, Dwiwahju; Indriani, Dea; Aditiawati, Pingkan (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTCharacterization of Lignite Biosolubilization Products by Indigenous Moulds from Soil ofCoal Mining in South Sumatera. Biosolubilization of coal is a potential technology of convertingsolid coal to liquid fuel and chemicals at ambient condition. Our previous research hassuccessfully isolated four moulds from soil at coal mining - South Sumatera and has potency aslignite biosolubilization agent, i.e. T1, T2, T4, T5. The objective of this research was to characterizeof lignite biosolubilization products by four isolates. The method used was sub-mergedculture. Cultivation medium was MSS+ (minimal salt + sucrose 0,1% + yeast extract 0,01% +lignite 5 %). Incubation was conducted at room temperature for 28 days. The result showed thatall indigenos moulds have different ability in lignite biosolubilization. The highestbiosolubilization occurred after 7 days of incubation belonging to T1 isolate. However, GC-MSanalysis showed the largest percentage of hydrocarbon compound which equivalent to gasolineand diesel was T5 after 7 days of incubation.Key words: Biosolubilization, lignite, moulds, coal.